The Role of Islamic Boarding Schools in Strengthening Students’ Digital Literacy and Religious Values in the Era of Society 5.0 - Madinatul Munawaroh (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2025)
This study explores the role of Islamic boarding schools (pesantren) in strengthening students’ digital literacy and religious values in the era of Society 5.0. Using a mixed-methods approach, data were collected from surveys, interviews, and classroom observations involving students, teachers, and administrators. Results show that pesantren successfully integrate digital skills with moral education, with religious values serving as the strongest foundation for responsible technology use. Digital literacy initiatives and teacher facilitation significantly enhance student preparedness, while infrastructure and access remain areas for improvement. The findings suggest that pesantren are capable of harmonizing tradition with modernity, producing graduates who are digitally competent, ethically grounded, and socially responsible.